The Relationship Between Occupation and Incidence of Various Types of Melanocytic Nevi - Riyanto, Puguh; Alexander, Lim (Jurnal Health Sains, 2025)
Melanocytic nevi (MN) are benign proliferations of melanocytes influenced by genetic and environmental factors, particularly ultraviolet (UV) radiation. Occupational exposure to sunlight may contribute to the development of different nevus types, but this relationship remains underexplored. This study aimed to examine the association between occupation and the incidence of various melanocytic nevi types. A descriptive observational study with a cross-sectional design was conducted among 20 participants in Semarang, Indonesia, from April to May 2025. Data were collected via validated questionnaires covering occupation (indoor/outdoor), protective measures (sunscreen, long-sleeved clothing), and nevus types (junctional, compound, intradermal). Statistical analysis was performed using SPSS. Results showed that 60% of participants had indoor occupations, while 40% worked outdoors. Among nevus types, 50% had compound nevi, 16% had junctional nevi, and 10% had intradermal nevi. A significant association was found between outdoor occupations and compound nevi (p = 0.010, RR = 3.50). No significant links were observed for junctional or intradermal nevi. Protective measures, such as sunscreen use, showed no significant impact, possibly due to low adherence (70% non-users). The findings suggest that occupational UV exposure may elevate the risk of compound nevi. Further research with larger samples and additional variables (e.g., sun exposure duration) is recommended to validate these results and to inform preventive strategies for at-risk populations.